Ankylosis of temporomandibular joint after the traumatic brain injury: a report of two cases. Issue 4 (19th October 2011) - Meng, Qinggong; Li, Bo; Long, Xing; Li, Jian; Yan, Quanmei
Abstract : Abstract –  Mouth opening limitation after the neurosurgical procedures is a common complication and usually resolves within 3 months. If limited mouth opening remains unresolved on the long term, an intra‐articular ankylosis of temporomandibular joint may develop eventually. The possible mechanisms base on the myositis and atrophy of the masticatory muscles for these craniotomies are often involved in the temporalis. This article reports two unusual cases with the intra‐articular ankylosis of temporomandibular joint after the traumatic brain injury, who received a modified surgical treatment for joint ankylosis. Therefore, the early diagnosis and intervention are important to minimize these complications.